89.8k views
0 votes
Can I know the steps​

Can I know the steps​-example-1
User Emmagras
by
5.4k points

1 Answer

5 votes

Explanation:

We are given:


xy'=coty

This can be rewritten as


x(dy)/(dx) =coty

Next, we can bring the x's and y's to their respective sides by dividing by coty and x and then multiplying the dx to the other side. We can then change
(1)/(coty) into
tany. This gives us the differential


tany\,dy=(1)/(x) \,dx

Now we can integrate each side


\int tan(y)\,dy=\int (1)/(x) \,dx

To integrate tan(y), we need to manipulate it


\int (sin(y))/(cos(y)) \,dy=\int (1)/(x) \,dx

Now we can use u-substitution where
u= cos(y)\\du=-sin(y) dy

This gives us


-\int (1)/(u) \,du=\int (1)/(x) \,dx

Now, lets integrate both sides


-ln|u|=ln|x|+c

Next, we can substitute our u value back in


-ln|cos(y)|=ln|x|+c

Now we can add
-ln|cos(y)| to the other side and subtract c from each side. This gives us


C_2=ln|x|+ln|cos(y)|

Next, we can apply a property of logarithms to combine this sum of two logs into one log.


C_2=ln|xcos(y)|

Lastly, we can add a base e to each side to remove the ln


C_3=|xcos(y)|

And here is our answer.

User Randall Stephens
by
4.8k points